A Study of Yemeni Secondary School Students’ Article Errors in their English Writing - Bushra Thabit Ahmed Qasem; Sabri Thabit Saleh Ahmed; Sunil V. Pawar (Journal of English Language Teaching and Linguistics, 2022)
This study has investigated Yemeni secondary school students’ articles errors with a reference to Labooza secondary school and AL-Samood secondary school in Radfan district. Data were collected through a writing test that targeted 100 students. The results revealed that 53.6% of students’ uses of the articles were wrong. It also showed that these errors can be subdivided into article omission errors 41.79%, article addition errors 23.88%, and article substitution errors 34.32%. These errors can be attributed to two sources, namely a- interference with students’ mother tongue (interlingual interference), constituting 39.93% and b- students’ insufficient knowledge of English articles as well as poor English teaching (intralingual), constituting 60.07%. As per these findings, these study provides some recommendations to syllabi designers, teachers and students of the Yemeni secondary schools.